The development of the controller for the HVAC system - Fu, Han (2019)
With the development of technology in the aspect of building and environment, people has already concerned about the nature environment and indoor environment which will influence daily life. As one of air-conditioning systems, the heating, ventilation and air-conditioning system comes into people’s sight with higher efficiency and lower energy consumption. What’s more, the system can bring comfort and health to people inside. From the details, the control of the system is crucial because it is the guarantee of functional integrity. Especially for the terminal unit, how to control the water valve and damper, how to choose suitable parameters for algorithms determine the quality of air supplied into conditioned rooms. In this dissertation, the importance of HVAC systems is emphasized, and the terminal unit is presented in detail. Then the complete procedure is described step by step and each device is introduced. It is the control logic which serves for the terminal unit decides the operation quality of the system. Another portion should be figured out is the hardware design, which needs appropriate electronic components to construct the control board waiting to be integrated with other components. After the design procedure, the accomplished board is applied to test its performance by installing it into the control cabinet to cooperate with other original boards. And the test result shows that the performance is satisfied and the system function is completed.